Hepatoprotective activity of aqueous methanolic extract of Morus nigra against paracetamol-induced hepatotoxicity in mice - Tauqeer Hussain Mallhi; M. Imran Qadir; Yusra Habib Khan; Muhammad Ali (Bangladesh Pharmacological Society, 2014)
Morus nigra (Family Moraceae) is traditionally used injaundice, diabetes, hypertension, cough, fever and cancer. The current study was conducted to determine hepatoprotective activity of aqueous methanolic extract of leaves of M. nigra. Two doses of 250 mg/kg p.o and 500 mg/kg p.o showed that extract of M. nigra produced significant (p<0.001) reduction in liver enzymes (ALT, AST, ALP) and total bilirubin induced by paracetamol and the results are comparable to silymarin (p<0.001). Results were supported by histopathological investigations, phytochemical screening and detection of active constituents by HPLC. The current study showed that aqueous methanolic extract of M. nigra possess hepatoprotective activity that might be due to quercetin, luteolin and isorhamnetin. It was concluded from this study that M. nigra has hepatoprotective activity against paracetamol induced liver injury in mice.